2006
DOI: 10.1038/sj.onc.1209899
|View full text |Cite
|
Sign up to set email alerts
|

A novel amplification target, DUSP26, promotes anaplastic thyroid cancer cell growth by inhibiting p38 MAPK activity

Abstract: Anaplastic thyroid cancer (ATC) is one of the most lethal of all human tumors, but cytogenetic information concerning ATC is extremely limited. Using our in-house array-based comparative genomic hybridization and 14 ATC cell lines with further fluorescence in situ hybridization analysis, we demonstrated amplification of the DUSP26 gene, known by another report as MAP kinase phosphatase-8. DUSP26 was overexpressed in ATC cell lines and primary ATC tumor samples. When overexpressed, either exogenously or endogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
100
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(104 citation statements)
references
References 42 publications
3
100
1
Order By: Relevance
“…As DUSP26 was previously shown to be amplified at the DNA level in anaplastic thyroid cancer (Yu et al, 2007), we performed fluorescence in situ hybridization analysis of DUSP26 with six neuroblastoma cell lines and found that DUSP26 is not amplified in these neuroblastoma cell lines (data not shown).…”
Section: Dusp26 Is Overexpressed In Majority Of Human Neuroblastoma Cmentioning
confidence: 94%
See 2 more Smart Citations
“…As DUSP26 was previously shown to be amplified at the DNA level in anaplastic thyroid cancer (Yu et al, 2007), we performed fluorescence in situ hybridization analysis of DUSP26 with six neuroblastoma cell lines and found that DUSP26 is not amplified in these neuroblastoma cell lines (data not shown).…”
Section: Dusp26 Is Overexpressed In Majority Of Human Neuroblastoma Cmentioning
confidence: 94%
“…Fluorescence in situ hybridization analyses were performed as described previously (Yu et al, 2007), using BAC RP11-258M15 clone located in the region of interest as probe.…”
Section: Immunoblotting and Immunoprecipitationmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also expressed at lower levels in the testis and thyroid gland (Wang et al, 2006) Localisation Dusp26 localizes to the nucleus and the cytoplasm (Takagaki et al, 2007;Vasudevan et al, 2005;Wang et al, 2006) Function At the molecular level, several Dusp26 substrates have been reported and we will briefly summarize them. Dusp26 was reported to dephosphorylate MAPKs such as p38, Erk and JNK, as well as Akt kinase,and to regulate their activity (Hu and Mivechi, 2006;Vasudevan et al, 2005;Wang et al, 2006;Wang et al, 2008;Yu et al, 2007). However, other authors have reported no effect of Dusp26 on MAPK, which suggests that this activity might not be the major function of the phosphatase, or that it might behave differently in different cell types (Patterson et al, 2010).…”
Section: Expressionmentioning
confidence: 99%
“…Comparative genome hybridization (CGH) shows frequent gain of 20q, including the UBCH10 gene in 20q13.12, which may also be associated with progression of differentiated thyroid cancers to ATC (Lee et al, 2007). Using microarray-based CGH with further fluorescence in situ hybridization (FISH) analysis, the MAP kinase phosphatase-8 (DUSP26) gene, which codes for a phosphatase that inhibits p38-mediated apoptosis, is shown to be amplified in ATC (Yu et al, 2007). Human telomerase reverse transcriptase (hTERT) protein expression is increased in ATC samples and cell lines (Takano et al, 2007).…”
Section: Cytogenetics Molecularmentioning
confidence: 99%